2010
DOI: 10.1007/s12032-010-9546-8
|View full text |Cite
|
Sign up to set email alerts
|

REG gamma: a potential marker in breast cancer and effect on cell cycle and proliferation of breast cancer cell

Abstract: To investigate the expression and significance of proteasomes reactivator REG gamma (γ) in breast cancer. First, we showed the expression of REGγ in breast cancer, metastatic lymph nodes and normal breast tissues. Meanwhile, we also analyzed the relationship between REGγ and estrogen receptor (ER), CerBb-2, lymph nodes metastasis and clinical stage of breast cancer. REGγ expression was determined by immunohistochemical staining and western blot. Secondly, we detected the expression of REGγ and REGγ-mRNA in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…Once pass the check point, cell cycle can be accomplished under the driver of cyclins and CDK even though the stimulation from growth factor is absent. It was showed that REGγ could promote HBL-100 cell to go from G1 into S phase (Wang et al, 2009). Therefore, these findings suggest that REGγ overexpression can promote laryngeal cancer cells proliferation and accelerate laryngeal cancer cells growth.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Once pass the check point, cell cycle can be accomplished under the driver of cyclins and CDK even though the stimulation from growth factor is absent. It was showed that REGγ could promote HBL-100 cell to go from G1 into S phase (Wang et al, 2009). Therefore, these findings suggest that REGγ overexpression can promote laryngeal cancer cells proliferation and accelerate laryngeal cancer cells growth.…”
Section: Discussionmentioning
confidence: 71%
“…For instance, REGγ has been reported to be highly expressed in thyroid cancer (Okamura et al, 2003) and in colorectal cancer serum (Roessler et al, 2006). Recently, the overexpressed REGγ has been also found in human breast cancer cells and the metastatic lymph nodes (Wang et al, 2009). On the basis of these observations, we presumed that REGγ may be highly expressed laryngeal cancer and have a role in the development of laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can promote the degradation of multiple proteins including p53 and MDM2 in an ubiquitin-and ATP-independent manner [1][2][3] . Previous studies found that REGg is overexpressed in numerous cancers including breast, thyroid, lung and liver cancers [4][5][6] , suggesting a potential role for REGg in tumorigenesis.…”
mentioning
confidence: 99%
“…It has been reported that REG could facilitate the growth of breast cancer cells. Abnormal high expression of REG has been observed in breast cancer and its metastatic lymph nodes (60). BCL2 has been introduced as an independent biomarker for prognosis of all types of earlystage breast cancers.…”
Section: Biomarkersmentioning
confidence: 99%